Things I have learned in my life so far - Sagmeister, Stefan
This book began as a list designer Stefan Sagmeister made in his diary under the title Things I have learned in my life so far, which includes statements such as Worrying solves nothing and Trying to look good limits my life. The list reveals something that is profoundly true: Although human beings have been pursuing happiness for countless generations, it is not so easily achieved. And we need constant reminders to keep us on the right path. With the support of his clients, Sagmeister transformed these sentences into typographic works, from billboards in France to sign toting inflatable monkeys on the streets of Scotland. Accompanied by essays from design historian Steven Heller, Guggenheim chief curator Nancy Spector, and UK psychologist Daniel Nettle, as well as Sagmeister's own words, the series is revealed as a complex blend of personal revelation, art, and design an eclectic mix of visual audacity and sound advice. This book consists of 15 unbound signatures in a laser cut slipcase. Shuffling the sequence of the signatures will produce 15 different covers